2018
DOI: 10.3390/ijms19103056
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Deletion of BAP1 and CDKN2A Are Useful Markers for Quality Control of Malignant Pleural Mesothelioma (MPM) Primary Cultures

Abstract: Malignant pleural mesothelioma (MPM) is a deadly cancer that is caused by asbestos exposure and that has limited treatment options. The current standard of MPM diagnosis requires the testing of multiple immunohistochemical (IHC) markers on formalin-fixed paraffin-embedded tissue to differentiate MPM from other lung malignancies. To date, no single biomarker exists for definitive diagnosis of MPM due to the lack of specificity and sensitivity; therefore, there is ongoing research and development in order to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…All samples obtained from previously diagnosed MPM patients were reviewed by an experienced pathologist (KL) with MPM-specific IHC markers before the experiments were carried out. Immunohistochemical analysis of MTAP (Abnova, H00004507-M01, 2G4 clone; 1/300 dilution) in MPM tissue samples was performed as described previously ( 7 ). Briefly, MPM cells and MPM tissue were processed for formalin fixed paraffin embedded (FFPE) block and were sectioned at 4 μ m thickness for IHC analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All samples obtained from previously diagnosed MPM patients were reviewed by an experienced pathologist (KL) with MPM-specific IHC markers before the experiments were carried out. Immunohistochemical analysis of MTAP (Abnova, H00004507-M01, 2G4 clone; 1/300 dilution) in MPM tissue samples was performed as described previously ( 7 ). Briefly, MPM cells and MPM tissue were processed for formalin fixed paraffin embedded (FFPE) block and were sectioned at 4 μ m thickness for IHC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently BAP1 and MTAP IHC have been used for this purpose with reasonably good sensitivity and specificity. However for equivocal cases, FISH for homozygous loss of CDKN2A ( 7 9 ) is often used to further differentiate between the two. We have previously shown that BAP1 and CDKN2A loss are frequent in MPM ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A general feature of a tumor is that it comprises tumor cells and stroma containing immune cells, fibroblasts, matrix and blood vessels. Therefore, it is not surprising that in this special issue, the mechanisms of mesothelioma heterogeneity have been addressed extensively at the level of tumoral cells, highlighting differences in genetic alterations [ 1 , 2 , 3 , 4 , 5 ] or temporal differences during tumor progression [ 2 ].…”
mentioning
confidence: 99%